Structures and processes for priority-setting by health-care funders: a national survey of primary care trusts in England - Robinson, Suzanne; Dickinson, H.; Freeman, T.; Rumbold, B.; Williams, I. (The Royal Society of Medicine Press, 2012)
Although explicit priority-setting is advocated in the health services literature and supported by the policies of many governments, relatively little is known about the extent and ways in which this is carried out at local decision-making levels. Our objective was to undertake a survey of local resource allocaters in the English National Health Services in order to map and explore current priority-setting activity. A national survey was sent to Directors of Commissioning in English Primary Care Trusts (PCTs). The survey was designed to provide a picture of the types of priority-setting activities and techniques that are in place and offer some assessment of their perceived effectiveness. There is variation in the scale, aims and methods of priority-setting functions across PCTs. A perceived strength of priority-setting processes is in relation to the use of particular tools and/or development of formal processes that are felt to increase transparency. Perceived weaknesses tended to lie in the inability to sufficiently engage with a range of stakeholders. Although a number of formal priority-setting processes have been developed, there are a series of remaining challenges such as ensuring priority-setting goes beyond the margins and is embedded in budget management, and the development of disinvestment as well as investment strategies. Furthermore, if we are genuinely interested in a more explicit approach to priority-setting, then fostering a more inclusive and transparent process will be required.